2012
DOI: 10.1007/s00198-012-1932-y
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of Radix Dipsaci total saponins on bone metabolism in vitro and in vivo and the possible mechanisms of action

Abstract: RTS treatment can effectively suppress the loss of bone mass induced by OVX and in vitro evidence suggests this could be through actions on both osteoblasts and osteoclasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…The anti-osteoporosis effect of RTS in vivo was systemically evaluated in a previous study by our group (20). In the present study, the effects of RTS on the osteogenic activities in MC3T3-E1 cells and the potential mechanisms of action were evaluated.…”
Section: A B C D Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The anti-osteoporosis effect of RTS in vivo was systemically evaluated in a previous study by our group (20). In the present study, the effects of RTS on the osteogenic activities in MC3T3-E1 cells and the potential mechanisms of action were evaluated.…”
Section: A B C D Discussionmentioning
confidence: 91%
“…A previous study by our group demonstrated that RTS effectively inhibited osteoporosis in ovariectomized rats. Additionally, RTS has been shown to enhance MC3T3-E1 cell differentiation, potentially due to its role in increasing the expression levels of BMP-2 (20). However, the detailed molecular mechanisms of the osteogenic effects of RTS remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Total flavonoid fraction of the Herb Epimedii extract prevented bone loss in OVX mice by increasing renal Ca re-absorption, stimulating the process of osteoblast formation as well as suppressing the process of osteoclastogenesis in OVX mice [ 43 ]. Radix Dipsaci extract prevented the loss of bone mass, enhanced the bone strength and prevented the deterioration of trabecular microarchitecture in OVX rats [ 44 , 45 ]. P soralea corylifolia L. extract and its main compound psoralen were reported to be able to decrease both urinary calcium excretion and serum osteocalcin in OVX rats that resulted in positive effects on maintaining BMD by increasing bone formation rate [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical properties of femurs were measured by the three-point bending test performed using a universal material test machine (AG-1S; Shimadzu Co., Kyoto, Japan) at room temperature, as described in previous studies (18)(19)(20). Briefly, the diaphysis was placed on two supports with a span of 10 mm, while the loading pin was centered above two supports at a displacement rate of 2 mm/min, until fracture occurred.…”
Section: Excess Iron Undermined Bone Load-bearing Capacity Through Tumentioning
confidence: 99%